Humidity Responsive Reflection Grating Made by Ultrafast Nanoimprinting of a Hydrogel Thin Film. Issue 19 (15th July 2022) - Cesnik, Stefan; Perrotta, Alberto; Cian, Alessandro; Tormen, Massimo; Bergmann, Alexander; Coclite, Anna Maria
Abstract: The response time of state‐of‐the‐art humidity sensors is ≈8 s. A faster tracking of humidity change is especially required for health care devices. This research is focused on the direct nanostructuring of a humidity‐sensitive polymer thin film and it is combined with an optical read‐out method. The goal is to improve the response time by changing the surface‐to‐volume ratio of the thin film and to test a different measurement method compared to state‐of‐the‐art sensors. Large and homogeneous nanostructured areas are fabricated by nanoimprint lithography on poly(2‐hydroxyethyl methacrylate) thin films. Those thin films are made by initiated chemical vapor deposition (iCVD). To the author's knowledge, this is the first time nanoimprint lithography is applied on iCVD polymer thin films. With the imprinting process, a diffraction grating is developed in the visible wavelength regime. The optical and physicochemical behavior of the nanostructures is modeled with multi‐physic simulations. After successful modeling and fabrication a first proof of concept shows that humidity dependency by using an optical detection of the first diffraction order peak is observable. The response time of the structured thin film results to be at least three times faster compared to commercial sensors. Abstract : A thin hydrogel film deposited by initiated chemical vapor deposition is nanostructured by ultrafast nanoimprint lithography to obtain a fast optical humidity sensor. The humidity responsive reflection grating shows response times way below commercial humidity sensors.